INSERÇÃO DO AFLORAMENTO CURVA II NO CONTEXTO TAFONÔMICO E ESTRATIGRÁFICO DA SEQUÊNCIA NEOPRAGUIANA – EOEMSIANA: INTERPRETAÇÃO PALEOAMBIENTAL DO SETOR NORDESTE DO SÍTIO URBANO DE PONTA GROSSA, PARANÁ, BRASIL - Myszynski Junior, Lucinei José (2012)
In this study we investigated the taphonomic and stratigraphic analyses of the basal layers of Sequence B (Neopraghiano / Eoemsiano), Ponta Grossa Formation, with a focus on Curva II outcrop, Ponta Grossa, Paraná, which until then had not been studied under these aspects. The objective is to provide a description and interpretation of the above mentioned outcrop, as well as the inclusion of its layers in stratigraphic framework of the sequence. In order to obtain more accurate data, the methodology used to collect data was of taphonomic high-resolution. The fauna here considered is a typical representative of the Malvinokaffric Realm and occurs distinctly along the Curva II outcrop. Three different taphocenosis representing different sedimentary environments have been identified. The data obtained in this study were integrated into the areas of occurrence of fossiliferous outcrops adjacent to Curva II. A combined analysis of the taphonomic, paleontological and stratigraphic aspects, followed by a reinterpretation of the outcrops in northeastern urban area of Ponta Grossa, inserts the Curva II outcrop above sections of the UEPG Campus, as well as Francelina I, II and III and below sections of Curva I and Franco da Rocha, which are representatives of a transgressive process, in a situation of sedimentary retrogradation which occurred in the passage Neopraghiano/Eoemsiano in the Ponta Grossa Formation, filling, thus, a gap in the stratigraphic sequence of the base of sequence B.